Blood Novels : Gender, Caste, and Race in Spanish Realism - Chang, Julia H. (Book collections on Project MUSE., 2022)
Blood Novels examines the significance of women's blood and bloodlines in nineteenth-century Spanish literature and culture, advancing the study of gender in modern Iberian studies.